Fenugreek Seeds Extracts as Growth Regulatory and Feeding Inhibitor for the African Melon Lady Bird Beetle Henosepilachna elaterii (Rossi) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study aimed at investigating the effect of the extracts offenugreek seeds on feeding and development of the African melonladybird beetle, Henosepilachna elaterii. (Rossi). Seeds of fenugreek(Trigonella foenum-graceum) were extracted by distilled water andorganic solvents (chloroform, acetone and ethanol), and the extracts weretested against the African melon ladybird beetle under laboratoryconditions. Both aqueous and organic extracts showed significant growthregulatory activities, mainly prolonging the larval duration. The effectwas clear in late instars. The organic extracts showed strong feedinginhibitory activity against the fourth larval instar, where the amounts offood consumed inversely related to dose. The effects induced by acetoneand ethanol extracts were greater than chloroform extract. Phytochemicalgroups present in various fractions were identified. Various aspects ofefficacy against the test insect are discussed
Keywords: Fenugreek; Henosepilachna elaterii; growth regulatory; feeding inhibitor